Vectors of development of energy cooperation between Russia and foreign countries under economic sanctions - I. S. Moga (Вестник университета, 2023)
The subject of this study is the modern aspects of Russia’s positioning in the global energy space. They are associated with the shift from the previously established liberal world order and the trend towards new polarisation in the world economic system, as well as with the increasing risks of turbulence in world energy markets. In this regard, it is extremely important to assess the real impact of economic sanctions on the nature of relationships and determine promising vectors for the development of energy cooperation between Russia and foreign countries. The research methodology includes analysis and synthesis methods and a historical approach, which are productively used to assess the tactical and strategic actions of our country in the system of international energy cooperation. The scientific novelty of the study lies in the substantiation of theoretical approaches and assessment of the practical implementation of energy cooperation with foreign countries. Those priority interests are considered that determine the economic sovereignty and identity of Russia in the conditions of a gradual but categorical shift of the world community from the previously established imperatives of liberalism and economic globalisation. The article is of an overview nature and describes the key areas of cooperation in the oil and gas and coal industries. Its main provisions may be used for long-term researches related to modernising the strategy of Russia’s foreign economic relations and increasing the level of its foreign economic security in the context of new global challenges.